1983
DOI: 10.1073/pnas.80.7.1972
|View full text |Cite
|
Sign up to set email alerts
|

Sequences related to HLA-DR alpha chain on human chromosome 6: restriction enzyme polymorphism detected with DC alpha chain probes.

Abstract: Three sets of cosmid clones-containing the HLADRa chain gene and two additional related genes-were isolated from human genomic DNA libraries by using a cDNA probe for the HLA-DRa chain. Southern blot analysis using DNA from somatic cell hybrids indicated that all of the clones mapped to chromosome 6. Partial sequence analysis showed that the two additional related genes were highly homologous to each other, and to the HLA-DRa chain, in parts of the exon that encoded the a2 domain but were more divergent in int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…In an attempt to define the molecular basis of the MT3 specificity, biochemical and restriction fragment length polymorphism studies have been conducted. These studies have revealed that cells typing as DR4, -7, and -9 contain a common fragment corresponding to the DQ a gene and this observation has led to the suggestion that the MT3 determinant represents a common structural component of DQ4, -7, and -9 a subunits (40,41). The studies presented here, which show strong structural similarity among the DQ4, -7, and -9 a subunits, would support this interpretation.…”
Section: Dq9supporting
confidence: 74%
“…In an attempt to define the molecular basis of the MT3 specificity, biochemical and restriction fragment length polymorphism studies have been conducted. These studies have revealed that cells typing as DR4, -7, and -9 contain a common fragment corresponding to the DQ a gene and this observation has led to the suggestion that the MT3 determinant represents a common structural component of DQ4, -7, and -9 a subunits (40,41). The studies presented here, which show strong structural similarity among the DQ4, -7, and -9 a subunits, would support this interpretation.…”
Section: Dq9supporting
confidence: 74%
“…A partial nucleotide sequence (data not shown) allowed us to identify the SB achain gene on the basis of its identity with a published sequence of an SB a-chain cDNA (22). From both restriction fragment size and partial sequence, this a-chain gene is homologous to the gene described by Trowsdale et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…Study of the DC subregion was initiated by isolation of DCa (8) and DCB cDNA clones (9), followed by isolation and sequencing of the corresponding genomic clones (10)(11)(12). When the isolated cDNA clones were used as probes, Southern blots of DNA from a homozygous cell line indicated the presence of two closely related a gene bands, named DCa and DXa (4,(13)(14)(15) and two (or more) / gene bands (12,(16)(17)(18)(19). A genomic clone for DXa was also isolated and sequenced (10).…”
mentioning
confidence: 99%